2016
DOI: 10.13189/sa.2016.041109
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Color in Healthcare Environments, Emergent Bodies of Evidence-based Design Approach

Abstract: The objective of this study is to overview the literature relative to color, as an environmental constituent, and its impacts in healthcare environments. Borrowing from the environmental behavioral paradigm, this study attempts to decipher myths and misconceptions as well as highlight well-evidenced research findings. Broad Literature review journal articles and reports of empirical studies in multiple disciplines were studied to identify theories, which could have design implications for color in healthcare d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
(85 reference statements)
0
20
0
1
Order By: Relevance
“…With evidence-based design perspective, architects and neuroscientists have engaged in a practice to promote human mental state, which focuses on increasing pleasantness in built environments (human-made environments; Papale et al, 2016). Studies have demonstrated a significant relationship between built environments and the human well-being using psychology and physiological indicators of wellness, such as measuring stress, moods, and cognitive performance (Adams, 2013; Cooper et al, 2014; Ghamari and Amor, 2016). Several studies have also demonstrated the significant impact of the built environments, such as the architectural styles (Choo et al, 2017), embodiment (Vecchiato et al, 2015), contours (Vartanian et al, 2013), height and enclosure (Vartanian et al, 2015), lighting and luminance color (Küller et al, 2009; Choi et al, 2014), built vs. natural environment (Sternberg, 2010; Roe et al, 2013; Banaei et al, 2015, 2017) on the subjects’ cortical activity and aesthetic judgments in architectural design.…”
Section: Introductionmentioning
confidence: 99%
“…With evidence-based design perspective, architects and neuroscientists have engaged in a practice to promote human mental state, which focuses on increasing pleasantness in built environments (human-made environments; Papale et al, 2016). Studies have demonstrated a significant relationship between built environments and the human well-being using psychology and physiological indicators of wellness, such as measuring stress, moods, and cognitive performance (Adams, 2013; Cooper et al, 2014; Ghamari and Amor, 2016). Several studies have also demonstrated the significant impact of the built environments, such as the architectural styles (Choo et al, 2017), embodiment (Vecchiato et al, 2015), contours (Vartanian et al, 2013), height and enclosure (Vartanian et al, 2015), lighting and luminance color (Küller et al, 2009; Choi et al, 2014), built vs. natural environment (Sternberg, 2010; Roe et al, 2013; Banaei et al, 2015, 2017) on the subjects’ cortical activity and aesthetic judgments in architectural design.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the strongest colour in the palette was a warm terracotta red (29YR 27/355) with an Light Reflectance Value (LRV) of 27 and a saturation of 355/1000. Under the poor lighting, however, this felt flat and carers suggested a more saturated, livelier red (10YR 21/436) despite having a lower LRV (22). This colour was placed at the most critical intersection with the aim of making a memorable place within the circulation (Figure 8).…”
Section: Project 1: Destinations and Directions For A Dementia Wardmentioning
confidence: 99%
“…A series of published papers provide useful summaries and recommendations based on literature reviews. Ghamari and Amor, 22 highlight the established benefits of colour in healthcare and make a case for further inter‐disciplinary research, but also stress the “incongruity and fragmentation of previous studies” and the widely different needs of the user groups. Reporting on their “Stressed Space” research project on architecture and mental health, Connellan et al identify a list of 13 themes ranked as priorities for design, which places “Light” (including sunlight, daylight, Circadian rhythms, and colour) as second to “Security,” with further references to colour crossing in‐between the “Therapeutic Environment” and “Interior Design.” They conclude that there is a lack of evidence‐based empirical research 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Ainda em relação a cor e luz como exemplo de itens ambientais de impacto sensorial; estudiosos afirmam que a ausência de iluminação natural adequada e a presença de iluminação artificial ininterrupta, com acréscimo cromático de alto valor (como pelo uso de revestimentos na cor branca ainda que de baixa intensidade de refletância) podem levar ao aumento do estresse, comprometimento da imunidade, termo regulação interrompida e delírio; tais fatores ainda podem dificultar o processo de cicatrização, postergando assim o período de permanência no local e, por fim, contribuir para o avanço da doença (DALKE et al,2006;MACALLISTER, 2016;GHAMARI;AMOR, 2016), mesmo que não conscientemente percebido. (ANDRADE; FERNAUD; LIMA, 2013).…”
Section: Breve Revisão E Considerações Da Ergonomia E O Local De Saúdeunclassified